HUBUNGAN STRES AKADEMIK DAN PSYCHOLOGICAL CAPITAL MAHASISWA SEMESTER ANTARA FAKULTAS PSIKOLOGI UNIKA ATMA JAYA JAKARTA - Stephanie Laurentia; Puji Tania Ronauli (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2022)
In order to succeed the implementation of the policy of Merdeka Belajar Kampus Merdeka in TheFaculty of Psychology Unika Atma Jaya, student class of 2019 and 2020 are required to take theshort semester. In fact, the short semester aims to give the benefit both students and universitiesso that the curriculum transformation could be well applied. However, the Short Semester isperceived as a tough academic requirement for students. Many students feel pressured to take theshort semester, especially during this pandemic. Therefore, to deal with academic stress, studentsneed to optimize their psychological capital so that they are able to deal with the learningdifficulties. Currently, the psychological capital approach is being developed in education andlearning. The aim of this study is to examine the relationship between academic stress andpsychological capital in semester students between FPUAJ. This study uses a quantitativecorrelation method to analyse the correlation between academic stress and psychological capitalof short semester students in Unika Atma Jaya. This study involves 109 participants (65participants from class of 2019 and 44 participants from class of 2020). The researcher used theStudent-Life Stress Inventory and PsyCap Questionnaire that is adapted to the study context andthrough the pilot study process. The results of the study shows that academic stress andpsychological capital have a significant negative correlation. These findings show that the higherthe psychological capital of students, the lower their academic stress level will be. Resiliency inpsychological capital has also been proven to be the dimension that has the biggest significantnegative correlation with academic stress than other psychological capital dimensions